Perspectives on Corporate Governance in State-Owned Enterprises: Evidence from Bosnia and Herzegovina, Croatia and Serbia - Sudžuka, Emir; Kulović, Dženan; Hruška, Domagoj; Nikolić, Jelena (Naše gospodarstvo/Our economy, 2025)
This paper examines the key aspects of corporate governance of state-owned enterprises (SOEs) through a comparative survey conducted in Bosnia and Herzegovina, Croatia, and Serbia. The research explores two distinct perspectives: the state’s view on the necessity and governance of SOEs, and the perspective of SOE boards on operational and strategic challenges. From the state’s perspective, the survey addresses issues such as the protection of national economic interests, state ownership in key industries, equitable service provision, and the reinvestment of SOE profits into public projects. Findings suggest a strong alignment among respondents across all three countries, supporting the idea that state ownership ensures economic sovereignty and guarantees fair access to essential services. On the other hand, the board perspective highlights concern about the bureaucratic barriers faced by SOEs, the influence of political interference on financial performance, and the limitations of public ownership in enhancing global competitiveness. Board respondents expressed the need for greater autonomy in decision-making and stressed the importance of partnerships with the private sector to optimise SOE efficiency and market position. The article synthesises these findings to address the broader question: Are SOEs essential in modern economies, or do they require reform to meet contemporary challenges? The results indicate that while SOEs hold strategic importance, reforms focused on reducing bureaucracy, enhancing governance, and promoting public-private partnerships are crucial for their future viability.